Direct and early complications of surgical treatment of infrarenal abdominal aortic aneurysm - طحان, حسين; غانم أحمد ,; حسام كنجو, (Latakia University Journal -Medical Sciences Series, 2022)
Introduction : Abdominal aortic aneurysm is considered a real threat to life, which requires monitoring or treatment, depending on the size or accompanying symptoms. The mortality rate can reach 80% in the event of its rupture. The main objective of the study is to determine the rate of direct and close complications of the surgical treatment of infrarenal abdominal aortic aneurysm and the search for risk factors in patients that predispose to the occurrence of such complications . Methods: The study included 72 patients (66 male, 6 female) whom ages range between (45-90) years {median=64.79} who had an infrarenal abdominal aortic aneurysm and who underwent selective surgery to repair it at Tishreen University Hospital in Lattakia during a period of 5 years between 2017-2021, where it was shown a prospective retrospective study on the mentioned sample . Results: Patients were followed up within 30 days of surgery. The total number of complications was 19, distributed among 12 patients. Pulmonary complications were the most common, and death occurred in 6 patients . Conclusion: this study suggests that there is a significant correlation between elective surgery and decreased complication and mortality of infrarenal abdominal aortic aneurysm .